Preservation of Cultural Heritage Using Virtual Reality Technologies and Haptic Feedback: A Prototype and Case Study on Antique Carpentry Tools - Antonya, Csaba; Butnariu, Silviu (MDPI AG, 2022)
Over the last decade, there have been intense concerns at the European and global level regarding the recovery, protection, and promotion of cultural heritage in various forms: monuments, historical sites, artifacts, cultural expressions. The world is becoming more and more aware of the loss of honor elements of cultural heritage due to the passage of time, natural or man-made disasters, negligence, and improper conservation. This paper aims to develop a tool to improve the visibility of elements that may become rare in everyday life over the coming years, becoming elements of cultural heritage. The paper refers to a haptic system for simulating kinematic and dynamic operating conditions based on an articulated mechanism, more precisely, the simulation of the operation of a manual saw as a carpentry tool, visualizing the sawing maneuver and increasing the level of understanding of the operation by the possibility of modifying the working parameters. In the developed virtual reality environment, the user’s perception can benefit by evoking two of their senses—the user can see the operation of the hand saw and can feel the manual process of cutting wood. User studies were carried out to evaluate the usability and performance of the virtual reality application. In two test scenarios, 20 people gave positive feedback in using custom-made haptic devices for various categories (engagement, manipulability, enjoyment, realism, usability, overall experience).
Keywords: cultural heritage; virtual reality; hand tools; manual saw; haptic system